(untitled) (Web of Teachers: Inderscience Research, 2024)
This article is about the role of the teacher in teaching foreign languages to different ages who want to speak a foreign language (English), and it is important to allow those who learn the language, as well as student-young people, it is important to form skills to allow them to think correctly, to listen to them even if they make a wrong statement, as well as to give their mistakes as feedback to themselves.